2018
DOI: 10.1136/ebmental-2018-300014
|View full text |Cite
|
Sign up to set email alerts
|

Ten simple rules for conducting umbrella reviews

Abstract: The current manuscript provides a practical guidance for conducting umbrella reviews in medical areas. Researchers, clinicians and policy makers might use the key points illustrated here to inform the planning, conduction and reporting of umbrella reviews in medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
365
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 433 publications
(373 citation statements)
references
References 36 publications
0
365
0
8
Order By: Relevance
“…This fragmented approach does not support optimal clinical decision-making,12 and the need for a robust method to summarise evidence across several, indeed many, interventions has been increasingly recognised 13. Network meta-analysis has been developed to (1) synthesise evidence across a network of randomised trials, (2) allow the estimation of the relative effectiveness of several interventions and (3) produce ranked treatment options 14.…”
mentioning
confidence: 99%
“…This fragmented approach does not support optimal clinical decision-making,12 and the need for a robust method to summarise evidence across several, indeed many, interventions has been increasingly recognised 13. Network meta-analysis has been developed to (1) synthesise evidence across a network of randomised trials, (2) allow the estimation of the relative effectiveness of several interventions and (3) produce ranked treatment options 14.…”
mentioning
confidence: 99%
“…The protocol of the review and the PRISMA checklist can be found along with this work into supporting information sections (see Supporting Information A and B). When possible and given that limited high‐quality evidence exists on the topic, essential key points of umbrella reviews were taken into consideration for the present work (Fusar‐Poli & Radua, ).…”
Section: Methodsmentioning
confidence: 99%
“…Implement evidence-based treatments for substance use disorders. Abundant research shows that these disorders are treatable and that people do recover when given evidencebased care, including behavioral therapies for all these disorders and medication-assisted treatments for alcohol and opioid use disorders and for smoking cessation 7,8 . However,…”
Section: Paolo Fusar-polimentioning
confidence: 99%